The Regulatory Framework of Forced Restructuring of Banks in the Polish Legal System - Paweł Szczęśniak (Societas et Iurisprudentia, 2019)
The presented paper deals with the issues concerning the means of forced restructuring of banks in the Polish legal system. The term “means of forced restructuring of banks” should be understood as a set of legal rules that allows to reorganise a bank under the threat of a bankruptcy. Forced restructuring is also referred as a special resolution regime. Means of forced restructuring constitute, in fact, an administrative method of affecting banks the functioning of which jeopardises the stability of financial system. The thesis of this paper constitutes the statement that means of forced restructuring create a coherent, complementary system of legal means that allows to reorganise national, i.e. domestic bank without spending public funds. Thanks to the means of forced restructuring, the responsibility for the bank losses, including the costs of its forced restructuring, remains with the shareholders or members of the bank as well as with its creditors, not with the state budget. Variability of using the means of forced restructuring allows to adjust the reorganisation process of the bank to the circumstances that relate to the bank itself and to the level of recession on the financial markets.